In silico Structural Characterization of Inflammasome Receptors in Multi Organ Dysfunction Syndrome - Aritonang, Erfan Andrianto; Muhammad Farid Rizal; Rahmawati Januar (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2026)
Multi organ dysfunction syndrome involves multiple inflammatory receptors that regulate multi-organ damage. This study aims to analyze the structural characteristics of multireceptor inflammasome through the in silico method. The receptors analyzed were TNFR1, IL-1, IL-6, and NLRP3. The structural characteristics analyzed include affinity energy, RMSD, inhibition constants, and amino acid interactions. The results showed that NLRP3 had the most negative affinity energy value compared to others, which was -9,4 kcal/mol and an inhibition constant of 0,237 μM. The validity of the NLRP3 model was confirmed to be very stable with an RMSD value of 1,1709 Å, while other receptors showed a structural deviation of > 6 Å. Amino acid interaction analysis showed that the majority of interactions occur hydrophobic more than other receptors, and there are also hydrogen bonds. Based on the results of the study, it is known that NLRP3 has the best structure in silico, so it can be used as a reference for receptor models in follow-up research related to pathogenesis and anti-MODS drug development studies